9
$\begingroup$

Show that for $B = (B_t)$ Brownian motion, its covariance is $cov(B_s, B_t) = min(s, t)$.

The solution I was given was:

For $s ≤ t$, $B_t = B_s + (B_t − B_s)$,

$B_sB_t = B_s^2 + Bs(Bt − Bs)$

$cov(B_s,B_t)=E[B_sB_t]$(as $E(B_i)=0)$

so $cov(B_s,B_t)=E[B_s^2]+E[B_s(B_t-B_s)]$,

as all increments of Brown motion are independent the second term in the RHS

$=E[B_s]E[B_t-B_s]=0*0=0$. Now $cov(B_s,B_t)=E(B_s^2)=Var(B_s)=s$.

Similarly if $t\leq s$ we get $=t$.

My question is, could I not have done this arguement the same way without assuming that $s\leq t$ in the first place? I mean, if $s\leq t$ why cant I say $B_s = B_t + (B_s − B_t)$ and conitnue like this to get the answer with a max instead of a min?

Is it because $B_t-B_s$ is only an increment if $t\geq s$? I mean otherwise we dont have independency or something?

$\endgroup$
1
  • 3
    $\begingroup$ Why don't you first assume $s \leq t$ without loss of generality? $\endgroup$ – Calculon May 8 '15 at 21:58
6
$\begingroup$

In your proof you use the fact that $B_s$ is independent of $B_t-B_s$ (indepedent increments) but this is only true if $s\leq t$.

$\endgroup$
1
  • $\begingroup$ thank you thats what I thought too $\endgroup$ – vounoo May 8 '15 at 21:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.